Language policies in Peru - Huayhua Pari, Felipe (2004)
While America presents a diversity in languages, cultures, ecology, climate, ethnicity, this diversity should not be a problem, but a possibility, a richness, a strengthening that we all have a moral obligation to maintain and not to end.